DAYA MENGIKAT PUTUSAN PANITIA PENGAWAS PEMILU DALAM PENYELESAIAN SENGKETA PEMILIHAN KEPALA DAERAH - Sabri Guntur (Lakidende Law Review, 2022)
This study aims to analyze the Binding Power of the Panwaslu's Decision in the dispute resolution trial for the parties, and to analyze whether the KPUD violates the law if it does not implement the Panwaslu's decision in the Settlement of Pilkada Disputes. This study uses a normative legal research type, in this case it is intended to conduct an assessment of the legal basis and legal doctrine related to the Binding Power of the Decisions of the Election Supervisory Committee in the Settlement of Regional Head Election Disputes. The legal material analysis technique used is prescriptive, in which the author provides a formulation of the concept of applying the rules of norms that can be used to solve the problems at hand. From this research, it can be seen that the binding power of the Panwaslu Decision in the settlement of regional election disputes based on Article 144 paragraph (1) of Law Number 10 of 2016 concerning the Second Amendment to Law Number 1 of 2015 concerning Stipulation of Government Regulations in Lieu of Law Number 1 of 2014 Regarding the Election of Governors, Regents, and Mayors to become a law, it is binding. So that it is clear to get legal certainty for the parties to the dispute, the administration, and the organizers. As well as requiring the KPU to carry out or follow up on the Panwaslu's decision, this is also regulated in Article 144 paragraph (2) of Law Number 10 of 2016, so that as a legal state that adheres to and is based on law, the KPU is obliged to comply with what is said. written in the rules. As part of the State Administration Officials and Election Organizers, the KPU is obliged to carry out the decision. And of course, sanctions must be given if they do not carry out the decision, because the KPU can be said to have violated the law.